On The Modification of Chaos Game Rules on A Square - Purnomo, Kosala Dwidja; Mawarni, Anindita Setya; Ubaidillah, Firdaus (BERKALA SAINSTEK, 2022)
Fractal is a collection of geometric patterns found in nature and can also be a mathematical model visualization in which the pattern is repeated on a different scale. The formation of a fractal object can be done with a rule called chaos games. Chaos games explain a dot that moves erratically. On this research there will be random and non-random modification of the chaos game rules on a square. The purpose of this research is to make modifications and get visual results from modifications of the rules random and non-random chaos game. Depictions of random and non-random chaos game are carried out using MATLAB programs. Visualization of the random chaos game rule modification is a new fractal object that has self-similarity. Whereas modifications of the non-random rules by giving a particular sequence in selection a square point result in convergent points at specific coordinates. This is demonstrated by showing the value of the limit from the distance between points that produced by non-random chaos game is zero.